DESIGN-BASED DEVELOPMENT OF CANAGLIFLOZIN ORODISPERSIBLE TABLETS: FORMULATION AND CHARACTERIZATION STUDIES - NAGA PHANI PJVV; RATNAMALA KV; RAMANA MURTHY KV (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study aimed to convert liquid self-microemulsifying drug delivery systems (SMEDDS) of canagliflozin into solid SMEDDS to enhance stability and develop an orally disintegrating tablet (ODT) formulation. The key goal was to improve disintegration time and in vitro drug release. Methods: Solidification of SMEDDS was achieved using two approaches: Adsorption onto carriers and lyophilization with mannitol. An I-optimal design was used to optimize the tablet formulation. Key variables included concentrations of super-disintegrants and adsorbents, while responses evaluated were disintegration time (R1) and in vitro drug release (R2). Aerosil 200 was used as the primary adsorbent, and croscarmellose as the super-disintegrant. Pre-compression parameters, such as flow properties, were analyzed based on different ratios of lactose and Aerosil 200. In addition, lyophilized formulations (L1-L4) were prepared and compared to adsorbed SMEDDS. Results: Disintegration time was significantly influenced by the concentration of the super-disintegrant, with croscarmellose promoting faster disintegration. Among the formulations, S6 demonstrated optimal characteristics, including a rapid disintegration time of 40 s and a high dissolution rate of 97.3%. Lyophilized formulation L4 showed the highest drug release (at 25 min), though adsorption onto Avicel proved superior in enhancing overall dissolution. Pre-compression evaluations confirmed improved flow properties with optimized ratios. Conclusion: Adsorption of SMEDDS onto solid carriers, particularly using Avicel, was more effective than lyophilization in improving dissolution and tablet performance. The optimized formulation (S6) exhibited robust characteristics suitable for long-term storage and use, demonstrating the potential of this approach for enhancing the bioavailability of poorly water-soluble drugs such as canagliflozin